Populism and the military: symbiosis and tension in Bolsonaro's Brazil. Issue 2 (17th February 2022) - Hunter, Wendy; Vega, Diego
ABSTRACT: Populist politicians surrounded by military allies are a frequent sight in countries that have experienced democratic backsliding. Populists sometimes seek protection in the military, who in turn leverage the relationship to advance their own interests. Despite the recent wave of populism, the burgeoning literature on it has not devoted due attention to analysing the populist-military relationship; its origins, outcomes, and tensions. This article analyses the Brazilian military's re-appearance under President Jair Bolsonaro. Absent the usual institutional support bases on which Brazilian presidents rely, Bolsonaro has cultivated military support with resources and positions that allow officers expanded political power and privilege. An equilibrium held for the government's first two years. Thereafter, growing reservations about propping up an increasingly unpopular president, especially by heeding orders that would threaten their professional integrity, put in question the future of the armed forces as a pillar of the Bolsonaro administration. At the same time, the military's substantial expansion in government and state positions under Bolsonaro raises the specter of elevated military autonomy under future administrations. This would be problematic for popular sovereignty, a cornerstone of democracy, even if uniformed officers are not saber-rattling, mounting coups or occupying presidential office.